2003
DOI: 10.1034/j.1399-3054.2003.00042.x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐dependent photosynthetic characteristics indicated by chlorophyll fluorescence in five mangrove species native to Pohnpei Island, Micronesia

Abstract: To investigate the adaptive capacity to strong light among mangrove species, we examined light-dependent properties of photosynthesis in relation to photoinhibition using chlorophyll fluorescence for sun-leaves of five mangrove tree species; Sonneratia alba, Rhizophora stylosa, Rhizophora apiculata, Bruguiera gymnorrhiza and Xylocarpus granatum. These species were classified into three groups; pioneer -S. alba and R. stylosa, intermediate -R. apiculata and B. gymnorrhiza and climax species -X. granatum. A furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…Also, since chronic photoinhibition occurs in a period of restrained growth, associated with a build-up in carbohydrate content (Silva et al 2004), it is unlikely that photoinhibition per se would largely result in decreased coffee productivity. Furthermore, photoinhibited outer leaves may play a role to attenuate light intensity and so protect inner leaves from photoinhibition (Kitao et al 2003). Finally, the present results suggest that shading would result in little, if any, additional photoprotection to the peripheral leaves.…”
Section: Discussionmentioning
confidence: 70%
“…Also, since chronic photoinhibition occurs in a period of restrained growth, associated with a build-up in carbohydrate content (Silva et al 2004), it is unlikely that photoinhibition per se would largely result in decreased coffee productivity. Furthermore, photoinhibited outer leaves may play a role to attenuate light intensity and so protect inner leaves from photoinhibition (Kitao et al 2003). Finally, the present results suggest that shading would result in little, if any, additional photoprotection to the peripheral leaves.…”
Section: Discussionmentioning
confidence: 70%
“…In addition, shade saplings of X. granatum surprisingly increased total leaf area to the same extent that sun saplings did (Fig. 4b), probably because of a negative influence of high light on sun leaves due to less effective protective mechanisms against photoinhibition (Kitao et al 2003).…”
Section: Discussionmentioning
confidence: 96%
“…a high turnover rate of leaves) is often associated with a higher relative growth rate and a higher photosynthetic assimilation rate (Reich et al 1991). Kitao et al (2003) reported that the light-saturated electron transport rate, which can be correlated with the photosynthetic rate, was highest in Sonneratia alba, followed by Rhizophora apiculata and Bruguiera gymnorhiza, and was lowest in Xylocarpus granatum (Avicennia alba was not measured). The result from the present study that leaf longevity is negatively correlated with RHGR in gaps implies that leaf-level traits (leaf turnover and photosynthesis) correspond directly to the individual-level growth rate in mangrove saplings.…”
Section: Discussionmentioning
confidence: 99%
“…Energy consumption via photosynthetic electron transport connected to PS II is an important factor in photoinhibition avoidance (Ö quist et al 1993;Baroli and Melis 1998;Kitao et al 2003Kitao et al , 2006b). In the present study, species with higher ETR capacity (Fig.…”
Section: Discussionmentioning
confidence: 99%